Shaping Professional Identity and Integrating Islamic Values in English Language Teaching: Evidence from a Pesantren Context - Mohammad Rosi Ilham; Bradhiansyah Tri Suryanto (CV. Publikasi Indonesia, 2026)
The professional identity of English teachers in Islamic educational contexts remains underexplored, particularly in Pesantren-based schools where academic education integrates with religious and moral development. English teachers in these settings face potential tensions between global language education and local cultural-religious values, yet limited attention has been given to how institutional, cultural-religious, and personal factors jointly shape their professional identity and how this identity is enacted through pedagogical decisions. This research investigates the factors shaping the professional identity of high school English teachers at Pondok Pesantren Nurul Jadid and examines how they balance English instruction with Islamic educational values. Employing a qualitative multiple case study design, the study involved six English teachers from three educational institutions within the Pesantren. Data were collected through semi-structured interviews, classroom observations, post-observation interviews, and document analysis, and were analyzed using thematic analysis. The findings show that teachers' professional identity is shaped through the interaction of institutional expectations, cultural-religious values, and personal beliefs, with teachers perceiving their roles as both language instructors and moral educators. Teachers balanced English instruction with Islamic values by integrating these values into classroom interaction, adapting materials to the Pesantren context, and embedding them across lesson planning, implementation, assessment, and reflection, while maintaining English as the primary instructional objective. This study contributes empirical evidence from the Pesantren context, demonstrating that professional identity in faith-based settings is reflected in teachers' pedagogical decisions, with implications for teacher development programs and further research across similar educational contexts.